In vitro reactivation of spindle elongation in fission yeast nuc2 mutant cells (The Rockefeller University Press, 1990)
To investigate the mechanisms of spindle elongation and chromosome separation in the fission yeast Schizosaccharomyces pombe, we have developed an in vitro assay using a temperature-sensitive mutant strain, nuc2. At the restrictive temperature, nuc2 cells are arrested at a metaphase-like stage with short spindles and condensed chromosomes. After permeabilization of spheroplasts of the arrested cells, spindle elongation was reactivated by addition of ATP and neurotubulin both at the restrictive and the permissive temperatures, but chromosome separation was not. This suggests that the nuc2 cells are impaired in function at a stage before sister chromatid disjunction. Spindle elongation required both ATP and exogenous tubulin and was inhibited by adenylyl imidodiphosphate (AMPPNP) or vanadate. The ends of yeast half-spindle microtubules pulse-labeled with biotinylated tubulin moved past each other during spindle elongation and a gap formed between the original half-spindles. These results suggest that the primary mechanochemical event responsible for spindle elongation is the sliding apart of antiparallel microtubules of the two half-spindles.